N,N,N′,N′-Tetraethyl-N′′-(2-fluorobenzoyl)phosphoric triamide - James A. Golen; Arnold L. Rheingold; Mehrdad Pourayoubi; Atekeh Tarahhomi (Acta Crystallographica Section E, 2011)
In the title compound, C15H25FN3O2P, the phosphoryl group is in an anti and syn orientation to the C=O and N—H groups, respectively. The P atom is in a distorted tetrahedral environment. One of the ethyl groups is disordered over two sets of sites with refined occupancies of 0.755 (6) and 0.245 (6). In addition, the F atom was refined as disordered with occupancies fixed at 0.9 and 0.1. This disorder corresponds to a rotation of approximately 180° of the fluorobenzene ring about its connecting C—C bond. In the crystal, pairs of intermolecular N—H...O(=P) hydrogen bonds form centrosymmetric dimers.